2016
DOI: 10.1103/physrevb.93.214430
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic ordering in the ultrapure site-diluted spin chain materialsSrCu1xNixO2

Abstract: Muon spin rotation technique is used to study magnetic ordering in ultra-pure samples of SrCu1−xNixO2, an archetypical S = 1/2 antiferromagnetic Heisenberg chain system with a small amount of S = 1 defects. The ordered state in the parent compound is shown to be highly homogeneous, contrary to previous report [M. Matsuda et al., Phys. Rev. B 55, R11953 (1997)]. Even minute amount of Ni impurities result in inhomogeneous order and a decrease of the transition temperature. At as little as 0.5 % Ni concentration,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…A similar asymmetry behavior has been observed also in other systems, including spin chains with bond-and site disorder, 32,33 or in iron-based superconductors at intermediate F doping. 34 In all these cases, the high sensitivity of µSR to chemical modifications emphasizes the delicate nature of the (originally) homogeneous magnetic order which, nevertheless, does not evolve to a different type of magnetic structure.…”
Section: Discussionsupporting
confidence: 82%
“…A similar asymmetry behavior has been observed also in other systems, including spin chains with bond-and site disorder, 32,33 or in iron-based superconductors at intermediate F doping. 34 In all these cases, the high sensitivity of µSR to chemical modifications emphasizes the delicate nature of the (originally) homogeneous magnetic order which, nevertheless, does not evolve to a different type of magnetic structure.…”
Section: Discussionsupporting
confidence: 82%
“…In this way, one establishes a rigorous mapping equivalence between the spin-1/2 Ising-Heisenberg ladder defined by the Hamiltonians (2), (3), (4) and, respectively, the mixed spin-(3/2,1/2) Ising-Heisenberg diamond chain with the nodal Ising spins S = 3/2 and the interstitial spin-1/2 Heisenberg dimers defined by the effective Hamiltonians (2), (11), (12). More importantly, it can be understood from the Hamiltonian (11) that the Ising inter-leg coupling J 0 gives rise to a uniaxial single-ion anisotropy acting on the effective spin-3/2 Ising variables, while the Ising intra-leg coupling J 1 produces unusual bilinear and higher-order (quartic) interactions between the Heisenberg and Ising spins.…”
Section: Ising-heisenberg Ladder With Alternating Inter-leg Intermentioning
confidence: 95%
“…The most widespread families of the spin-1/2 Heisenberg ladder materials are cuprates Cu 2 (C 5 H 12 N) 2 Cl 4 [7], SrCu 2 O 3 [8], (C 5 H 12 N) 2 CuBr 4 [9], and vanadates M 2+ V 2 O 5 [10], (VO) 2 P 2 O 7 [11], which involve Cu 2+ and V 4+ magnetic ions as the spin-1/2 carriers. Recently, another experimental realization of the spin-1/2 Heisenberg two-leg ladder Cu(Qnx)(Cl 1−x Br x ) 2 , where Qnx stands for quinoxaline (C 8 H 6 N 2 ), has opened up a new opportunity to continuously tune the inter-leg to intra-leg coupling ratio albeit in a relatively narrow range [12].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Recent experiments have demonstrated that when impurities are added to prototypical Heisenberg Antiferromagnetic (HAF) S = 1/2 chain materials SrCuO 2 and Sr 2 CuO 3 , their magnetism is suppressed. [11][12][13][14][15][16] Long range magnetic ordering arising from residual three-dimensional interactions becomes inhomogeneous and occurs at lower temperatures. 11,16 Additionally, the spin-lattice relaxation rate 1/T 1 measured by NMR experiments drops at low temperatures, suggesting a depletion of low energy excitations.…”
Section: Introductionmentioning
confidence: 99%